Growth Factors as Axon Guidance Molecules: Lessons From in vitro Studies - Onesto, Massimo M.; Short, Caitlin A.; Rempel, Sarah K.; Catlett, Timothy S.; Gomez, Timothy M. (Frontiers in Neuroscience, 2021)
Growth cones at the tips of extending axons navigate through developing organisms by probing extracellular cues, which guide them through intermediate steps and onto final synaptic target sites. Widespread focus on a few guidance cue families has historically overshadowed potentially crucial roles of less well-studied growth factors in axon guidance. In fact, recent evidence suggests that a variety of growth factors have the ability to guide axons, affecting the targeting and morphogenesis of growth cones in vitro. This review summarizes in vitro experiments identifying responses and signaling mechanisms underlying axon morphogenesis caused by underappreciated growth factors.